A Heterostructure‐In‐Built Multichambered Host Architecture Enabled by Topochemical Self‐Nitridation for Rechargeable Lithiated Silicon‐Polysulfide Full Battery. (19th June 2021) - Wei, Yunhong; Zhang, Mi; Yuan, Li; Wang, Boya; Wang, Hongmei; Wang, Qian; Zhang, Yun; Guo, Junling; Wu, Hao
Abstract: Metal nitride‐based heterostructures have been effective polysulfide mediators in lithium‐sulfur batteries. Still, these heterostructures developed so far primarily rely on high‐temperature ammonification with corrosive NH3 or synthetic nitrogen‐contained reagents as nitrogen sources, casting potential environmental hazards, and additional technical challenges. Herein, a multichambered carbon nanofiber host architecture with an in‐built TiN/TiO2 heterostructure configuration derived from natural structured proteins is designed. The TiN/TiO2 heterostructure is spontaneously generated in the carbon nanofibers upon the pyrolysis of inborn N‐enriched bio‐precursor accompanied by thermal‐induced topochemical self‐nitridation without any additional nitrogen sources. Ex‐/in situ experiments with theoretical calculations identify the strong trapping and enhanced charge transfer on the polar heterointerfaces, synchronously realizing the immobilization–diffusion–transformation of polysulfides. The multichambered host framework with rich internal voids and enhanced conductivity promise the accommodation of liquid Li2 S6 catholyte, meanwhile ensuring that the cells can work with lean electrolyte. Consequently, the resulted Li‐polysulfide cell exhibits an ultralow capacity decay of 0.023% per cycle over 500 cycles and considerable areal capacity (≈6 mAh cm –2 ) at high S loading (5.8 mg cm –2 ). Importantly, an ingenious configurated full battery based on lithiated silicon anode and polysulfide cathode is competent to achieve appreciable cyclability with high energy density even under a low negative/positive capacity ratio (≈1.18). Abstract : A "multistorey residential building"‐resembled heterostructure‐in‐built multichambered nanofiber host architecture is constructed via topochemical self‐nitridation without any additional nitrogen sources, which can synchronously realize the immobilization‐diffusion‐transformation of polysulfides and the development of high‐energy‐density lithiated silicon‐polysulfide full batteries.